OPTIMIZING THE ROLE OF SCHOOL LIBRARIES IN IMPROVING STUDENTS' READING INTEREST IN THE DIGITAL ERA (CASE STUDY OF SMPN 15 MATARAM) - Sa'adiah, Halimatun; -, Ridwan; Ayu Hapsari, Nurul Fikriati; -, Rohana (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
In today's information era, digital transformation of school libraries is a major strategy in increasing students' interest in reading. This study analyzes the implementation of an automation system based on SLiMS (Senayan Library Management System) and a physical literacy program in optimizing the role of the library at SMPN 15 Mataram. The approach used is descriptive qualitative with a case study method, and data collection through observation, interviews, and documentation. Data analysis was carried out using the Miles, Huberman, and Saldana model which includes reduction, presentation, and drawing conclusions. The results of the study show that by April 2025, 1,000 out of 2,000 book collections have been successfully inputted into SLiMS, which contributes to increasing the efficiency of collection management and readiness of digital services. The reading garden and reading corner programs in the classroom increase student interaction with informal reading materials by 40%. The novelty of this study lies in the simultaneous integration of digital transformation and physical space-based literacy, which produces a contextual digital literacy ecosystem model. The practical contribution of this study is in the form of recommendations for tiered implementation strategies that combine digitalization and participatory literacy to create adaptive and sustainable school libraries.